(untitled) (Al-Academy, 2023)
In recent years, the means of communication have achieved a great generality that made them occupy, in a short time, the first ranks among the most widely used social networks in the world, due to the many services and advantages offered by this network to its users. It has led to a leap in the field of visual communication, especially since it relies mainly on the image Its dimensions make it a means of communication and transfer of ideas and meanings between the peoples of the world, and it also allows the inclusion of digital advertising content using multimedia with a degree of professionalism in other social networks, which allowed the various segments of society the opportunity to invest this network in their businesses of different orientations and goals. Especially with regard to the degree of digital maturity and awareness of the importance of these communication media among those in charge of the economic field in Iraq. Keywords (digital marketing, communication, promotion) The research included four chapters that defined the theoretical framework of it in three sections and dealt with the following topics: (marketing foundations between the concept and objectives, the effectiveness of communication means and their transformations in the management of marketing and digital promotion, digital promotion and its impression on the user), then the research dealt with indicators from which the theoretical framework came out. As for the third chapter, the researchers dealt with the procedures that it carried out, which included the research methodology by choosing the descriptive approach for the purposes of analysis, adopting the intentional sample method in selecting the sample models, as (3) models were chosen from the research community with a rate of (60%) from the original community, then The fourth chapter is devoted to presenting and discussing the results and conclusions, as it came from them:1. The communication means of digital marketing through advertising ideas gave influence and persuasion of the product through the offers and facilities provided by companies to enhance their marketing goals in a way that suits the user, and this appears in all research samples.2. Achieved the effect of social networking pages, including Facebook, for companies to promote their advertisements in an effective and simple way to reach the user in the use of publishing and promotion. The research also included a set of recommendations and proposals, a list of sources, appendices, and an abstract in English